Relevance of the use of measurement units and orders of magnitude in the training of civil engineers (2021)
Worldwide, a typical civil engineering program focuses in formal, natural, and applied sciences within an environment of ethical and social responsibility. Mathematics and computer sciences are the main formal sciences. The most widely used natural sciences are physics, earth science, and chemistry. On the other hand, a student who begins the professional cycle of the program must develop skills in applied science to solve practical problems. Complex processes and concepts requiring skills related to mathematics and physics must be developed. Such processes and concepts demand an impeccable handling of operations which involve diverse precision degrees, measurement units and a high variety of basic and derived quantities. This work describes the identification and classification of the main errors made by students when solving written exams applied in a natural environment of structural design courses. Data were collected during four years at a university in Colombia. Report of errors was grouped into five categories named modelling, quantities, regulation, signs, and others. Collected errors were evaluated qualitatively and quantitatively. In addition, each error was assigned to a risk level (high, intermediate, low) according to its potentiality to generate catastrophic errors in professional practice. The quality and number of observed errors seem to be correlated with the time of year in which they occur. On the other hand, the high-risk errors resulted to outweigh the two lower risk levels. This finding is worrying and serves as the basis for making an urgent call to review the way of teaching and its relationship with practical results. In synthesis, this study presents a novel manner to study the formation errors in engineering civil programs. In the near future, it is expected to use the results of this research to propose a procedure for the design and feedback of teaching strategies consistent with the evaluation objectives of each course.